Falcon Neuro space-based observations of lightning using event-based sensors - McHarg, Matthew G.; Jones, Imogen R.; Wilcox, Zachary; Balthazor, Richard L.; Marcireau, Alexandre; Cohen, Gregory (Frontiers in Remote Sensing, 2024)
The observation of lightning from space can have several advantages, including views of the tops of clouds, that can facilitate the study of in-cloud lightning as well as the world-wide access provided by the orbital parameters of a satellite. Given the brief duration of lightning, current space-based lighting monitors are necessarily complex in order to resolve both the spatial and temporal features of lighting discharges. Event-based sensors provide a new low-cost way of using a commercial camera to study lightning from space. The Falcon Neuro mission comprises two event-based vision sensors attached to the Columbus Module of the International Space Station. Its mission is to detect lightning and related electrical discharges in the Earth’s atmosphere. We report here on initial data collection and analysis of lightning by the United States Air Force Academy and Western Sydney University.